(untitled) - Richards, Jack C (Cambridge, 1997)
New Interchange is a multi-level series for adult and young adult learners of English from the beginning to the high-intermediate level. The Teacher's Manual contains teaching suggestions, answer keys for the Student's Book and Workbook, listening scripts, optional activities, and photocopiable Achievement Tests with their own listening scripts and answer keys
Keywords: English language,Tiếng Anh; Study and teaching,Foreign speakers,Dạy và học,Người nước ngoài